Pet ownership and children's self-esteem in the context of war - Keresteš, Gordana (Array, 1999)
The aim of the study was to examine possible beneficial effects of pet ownership on self-esteem of war-traumatized school children. The Croatian version of Rosenbergs Self-Esteem Scale was administered on a three groups of elementary school children of both sexes, grades 5th to 8th, all severely affected by war: dog- or cat-owners (N=295), owners of other kinds of animals (N=144), and non pet-owners (N=173). There were no differences between groups on basic socio-demographic variables. It was hypothesized that war-traumatized pet-owners, especially owners of dogs and cats, would have higher self-esteem than war-traumatized non pet-owners. Sex and age differences in self-esteem were also examined. The results of the three-way ANOVA (Pet Ownership ´ Sex ´ Age) have shown that only age had significant effect on self-esteem, with fifth and sixth graders having higher self-esteem than seventh and eight graders. Thus, the hypothesis that pet ownership could have beneficial effects on self-esteem of war-traumatized children was not supported. The importance of more precise measures of pet-child relationship was emphasized.